Youth Entrepreneurship – The role of Entrepreneurship in Opportunity Development in UK job market - Gupta, Payal (2012)
“We must develop strategies that give young people everywhere a real chance to find decent and productive work which will allow them to become independent and responsible young citizens” -Kofi Annan, UN Secretary- General, International Youth Dar (2003) (Ref: Arzeni. S and Mitra. J, 2008) UK has high rate of unemployment among young people. Entrepreneurship has been increasingly recognised as a source of creating jobs and empowerment, but not much attempts have been made to look it from the viewpoint of creating livelihood through entrepreneurial activities. It can also be looked upon as a tool for employing youth during recession and under severe unemployment in UK. Young people can forge a livelihood through creating an enterprise which further leads to many economic and social opportunities. Joblessness acts a push factor which propels youth to become ‘necessity entrepreneurs’ (GEM 2005). Entrepreneurship is considered as an innovative methodology to integrate youth into today’s labour market. It is accepted as an important means, an additional strategy to create jobs, improve livelihood and make young people economically independent (Schoof. U, 2006). The main aim of the report is thus to stimulate the benefits of youth entrepreneurship as a career, further on understanding the obstacles, role of mentoring in entrepreneurship and the policies and programmes to support it in UK. The report, therefore, draws the data from a variety of sources upon which the analysis is based.